Α-Hydroxy boron-enabled regioselective access to bifunctional halo-boryl alicyclic ethers and α-halo borons. Issue 37 (12th April 2021) - Wang, Lucia; Lin, Shengjia; Zhu, Yawei; Ferrante, Daniel; Ishak, Timaf; Baba, Yuki; Sharma, Abhishek
Abstract : Two new applications of alpha-hydroxy borons have been developed leading to a regioselective access to hitherto unknown halo-boryl alicyclic ethers and rare secondary alkyl alpha-halo MIDA boronates. Abstract : α-Hydroxy borons are an underutilized class of compounds and their only previous application involved oxidation into acylborons. Herein, we describe the synthesis of functionalized olefinic α-hydroxy borons and their utility to enable a novel and regioselective route to hitherto unknown bifunctional halo-boryl tetrahydrofurans/tetrahydropyrans and α-halo MIDA boronates. The orthogonally functionalized alicyclic ethers provided a building block-based approach for diversification of the tetrahydrofuran core.